2009
DOI: 10.1097/aco.0b013e32832a1d1b
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and epidural analgesia during labour

Abstract: There is no good evidence that epidural analgesia causes reduced breastfeeding success. Good lactation support is critical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Many factors, such as the mode of delivery, prior breastfeeding success, and parity, are considered potentially confounding variables in evaluating analgesia labor effect on breastfeeding. 6,7,27 For this reason, in our study we excluded patients with potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many factors, such as the mode of delivery, prior breastfeeding success, and parity, are considered potentially confounding variables in evaluating analgesia labor effect on breastfeeding. 6,7,27 For this reason, in our study we excluded patients with potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding has significant benefits for the newborns (i.e., protection from infectious diseases, improved cognitive development, and benefits related to maternal-infant bonding). 6 Human milk may also protect against sudden infant death syndrome, diabetes, lymphoma, allergies, and chronic digestive diseases. Lactation decreases the risk of postpartum bleeding, speeds the return to prepregnancy weight, improves bone remineralization, and reduces risks of ovarian and breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, other studies found no such relationships (17, 23-27), including one randomized clinical trial (6). Some argue that this one trial has settled the discussion about a potential deleterious relationship between breastfeeding and use of epidural (28) As with many of the epidural and breastfeeding studies, the trial’s analyses did not include covariates well-known to be associated with breastfeeding (e.g. breastfeeding intention, goal; marital/partner status).…”
Section: Introductionmentioning
confidence: 99%
“…At hospitals with policies that minimize early maternal-infant separation, when analgesia is required, epidural labor analgesia is the best form of analgesia available, because it has minimal effects on the newborn and lactation success [43,46,47].…”
Section: Neuraxial Analgesia During Labormentioning
confidence: 99%